Tanggung Jawab Perusahaan Terhadap Pemenuhan Upah Pekerja dalam Proses Pemberesan Boedel Pailit - Iustika Puspita Sari; Ahyuni Yunus (University of Udayana, 2019)
This study aims to analyze the problems of the Company's Responsibility towards Fulfilling the Wages of Employees in the Bankruptcy Boedel Delivery Process; And to find out the factors that inhibit the prior rights of fulfilling the wages of workers in the process of bankruptcy in Boedel. The study used the Normative-Empirical Legal Research method. The Results of the Study Show That: First: The Responsibility of the Company for the Fulfillment of Workers' Rights in the Process of Bankruptcy Boedel Giving Based on the Emergence of Rights and Obligations Between Entrepreneurs and Workers Poured in Work Agreements as Strong Engagement for the Fulfillment of Rights and Obligations (Achievements ) Each Party. Legal Protection of Workers' Rights in the Process of Bankruptcy Boedel Giving Can Be Taken Through 3 (Three) Ways, Namely: 1. Strengthening the Position of the Priority Rights of the Workers / Laborers in the Law, Especially the Bank Law; Second: Factors that Inhibit the Priority Rights of Fulfillment of Workers' Rights in the Process of Bankruptcy Boedel Giving Is Weak Supervision, Absence of Sanction Enforcement and Lack of Transparency in the Process of Bankruptcy of Boedel Companies Penelitian ini bertujuan untuk menganalisis permasalahan Tanggung Jawab Perusahaan Terhadap Pemenuhan Upah Pekerja Dalam Proses Pemberesan Boedel Pailit; Serta Untuk Mengetahui Faktor Yang Menghambat Hak Mendahulu Pemenuhan Upah Pekerja Dalam Proses Pemberesan Boedel Pailit. Penelitian menggunakan metode Penelitian Hukum Normatif-Empiris. Hasil Penelitian Menunjukkan Bahwa: Pertama: Tanggung Jawab Perusahaan Terhadap Pemenuhan Hak-Hak Pekerja dalam Proses Pemberesan Boedel Pailit Adalah Berdasar Pada Timbulnya Hak Dan Kewajiban Antara Pengusaha Dan Pekerja Yang Dituangkan Dalam Perjanjian Kerja Sebagai Perikatan Yang Kuat Untuk Pemenuhan Hak Dan Kewajiban (Prestasi) Masing-Masing Pihak. Perlindungan Hukum Atas Hak-Hak Pekerja (Buruh) Dalam Proses Pemberesan Boedel Pailit Dapat Ditempuh Melalui 3 (Tiga) Cara, Yakni: 1. Mempertegas Kedudukan Hak Mendahulu Pihak Pekerja/Buruh Dalam Undang-Undang, Khususnya Undang-Undang Kepailtan; Kedua: Faktor Yang Menghambat Hak Mendahulu Pemenuhan Hak-Hak Pekerja (Buruh) Dalam Proses Pemberesan Boedel Pailit Adalah Lemahnya Pengawasan, Tidak Adanya Penegakan Sanksi Serta Kurangnya Transparansi Dalam Proses Pemberesan Boedel Perusahaan Pailit.